Aortic Balloon Occlusion Technique Does Not Improve Peri-Operative Outcomes for Acute Type A Acute Aortic Dissection Patients With Lower Body Malperfusion - Tong, Guang; Sun, Zhongchan; Wu, Jinlin; Zhao, Shuang; Chen, Zerui; Zhuang, Donglin; Liu, Yaorong; Yang, Yongchao; Liang, Zhichao; Fan, Ruixin; Sun, Tucheng (Frontiers in Cardiovascular Medicine, 2022)
Background: The management of malperfusion is vital to improve the outcomes of surgery for acute type A acute aortic dissection (ATAAD). Open arch repair under hypothermic circulatory arrest with selective antegrade cerebral perfusion (HCA/sACP) is safe and efficient but associated with inevitable hypothermia and ischemia-reperfusion injury. The aortic balloon occlusion (ABO) technique is shown to be organ protective by allowing higher temperature and shorter circulatory arrest time. In this study, we aimed to evaluate the safety and efficacy of this new technique for ATAAD patients with lower body malperfusion. Methods: Between January 2013 to November 2020, 355 ATAAD patients with lower body malperfusion who underwent arch repair in our institute were enrolled. The patients were divided into 2 groups: ABO group (n = 85) and HCA/sACP group (n = 271). Propensity score matching was performed to correct baseline differences. Results: 85 pairs were generated by propensity score matching. Circulatory arrest time was significantly lower in the ABO group compared with the HCA/sACP group (median, 8 minutes vs 22 minutes; P<.001). The incidence of in-hospital mortality (10.6% vs 12.9%; P =.812), stroke (7.1% vs 7.1%; P =1.000), dialysis (25.9% vs 32.9%; P =.183), hepatic dysfunction (52.9% vs 57.6%; P =.537), tracheostomy (4.7% vs 2.4%; P =.682), paraplegia (1.2% vs 4.7%; P =.368) were comparable between ABO and HCA/sACP groups. Other outcomes and major adverse events were comparable. Multivariable logistic analysis did not recognize ABO technique protective against any major adverse outcomes. Conclusions: For ATAAD patients with lower body malperfusion, the ABO technique allows the performance of arch repair with FET under higher temperature and shorter circulatory arrest time. However, ABO technique did not improve perioperative outcomes. Future studies are warranted to evaluate the efficacy of this technique.